Integration of expectation confirmation theory and self-determination theory in internet banking continuance intention. Issue 3 (29th January 2019) - Rahi, Samar; Abd. Ghani, Mazuri
Abstract : Purpose: The expansion of information technology (IT) has become a great challenge in the business world today. Benefits from IT investment are only realized through sustained usage, rather than initial acceptance. Therefore, designing strategies continuously attracting user retention is the most critical and general question in IT global market. This paper aims to develop an integrated model that combines two well-known theories expectation confirmation theory (ECT) and self-determination theory (SDT) to determine customer's continuance intention toward use internet banking. Design/methodology/approach: A total number of 398 customers of commercial banks participated in this research. The research model was empirically tested using structural equation modeling. Findings: The findings reveal that both ECT and SDT have significant influence in a customer's continuance usage intention. The integrated model has good explanatory power (76.3%) to predict customer's continuance intention toward use of internet banking. Additionally, importance performance matrix analysis indicates that intrinsic regulation and customer's satisfaction are the most important factors to determine internet banking user's continuance intention. Practical implication: Internet banking users will be intrinsically motivated only for those activities that generate intrinsic interest for them, activities that have the charm of novelty, challenge or aesthetic significance. Thus, understanding banking customer intrinsic values should be a priority for managers and policymakers. Theoretically, integration of two well-known theories, ECT and SDT, provide basis for further refinement of technology continuance model in emerging e-payment domain. Originality/value: This study is different from several traditional studies that had investigated initial acceptance of internet banking. In contrast, this study provides a comprehensive analysis of customer's behavior in continuance intention context with technology (ECT) and motivational factors (SDT).